Analisis Kelayakan Ekonomi dan Perencanaan Struktur Gedung Politeknik Kesehatan Kementerian Kesehatan (Poltekkes Kemenkes) Provinsi Bengkulu - Horasian Tarihoran; Rezi Munizar; Yoka Mahendra (Journal of Engineering and Applied Technology, 2026)
The Bengkulu Health Polytechnic of the Ministry of Health (Poltekkes Kemenkes Bengkulu), located at Jl. Indragiri No. 3, Padang Harapan, Bengkulu City, has experienced continuous growth in student enrollment, resulting in increasing demand for classrooms and laboratory facilities. This study aims to design a new building structure that complies with Indonesian National Standards (SNI) and to evaluate the economic feasibility of the proposed construction project. The research employed reinforced concrete structural design based on SNI 1727:2020 and SNI 2847:2019, combined with an economic feasibility analysis using Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), Payback Period (PP), and sensitivity analysis. The results indicate that the proposed structural dimensions satisfy the required structural safety criteria, while the economic evaluation yields an NPV of IDR 6.75 billion, an IRR of 10.8%, a BCR of 1.32, and a payback period of approximately 12 years and 4 months, confirming the project's feasibility. Sensitivity analysis further indicates that the project remains feasible under construction cost increases of up to 20%, although higher interest rates approaching 10% reduce its economic margin.